The field guide to citizen science : how you can contribute to scientific research and make a difference - Cavalier, Darlene; Hoffman, Catherine; Cooper, Caren B. (Caren Beth) (Timber Press Inc., 2020)
This hands-on guide to citizen science details how ordinary people can participate in scientific research and help change the world in meaningful ways.